Social networks in non-profit organizations - Ivana Vidak; Dejan Tubić; Martina Kovačević (Mednarodno Inovativno Poslovanje)
The purpose of this paper is to define the communication, communication process, the concept of social networks and non-profit organizations, with special emphasis on how non-profit organizations use social networks for their work. Social networks are a form of everyday private or business communication. There are different types of social networks, and some of the most popular are: Facebook, WhatsApp, Messenger, Instagram, YouTube, TikTok. The goal of public relations is to provide the organization with an environment in which it will function best and where it will have the opportunity to build its reputation. In the second part of the paper, research methodology is to give through a comparative analysis of the use of social networks as a communication tool in the interpersonal communication of non-profit organizations with users. A descriptive analysis was conducted between ten non-profit organizations in the Republic of Croatia. Conducted analysis has shown that non-profit organizations use social networks in their daily work, for communication, but also for transparency of their work. In further research it would be advisable to detect who are stakeholders in such communication process and what is their opinion or suggestions for non-profit organization.